1989
DOI: 10.1159/000266815
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biometry of the Anterior Eye Segment

Abstract: In this paper, a method is presented to evaluate the true values of several optical parameters of the anterior eye segment. These are: the thicknesses of the cornea and lens, the depth of the anterior chamber and the anterior and posterior curvatures of the cornea and lens. First, a photo is taken of each patient’s eye with a Topcon SL-45 Scheimpflug camera. There are two effects distorting the photo. As the film plane and the object plane are perpendicular to each other, the imaging scale is not constant over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…However, both techniques, A scan ultrasonography and slitlamp Scheimpflug photography, have their respective drawbacks: ultrasonography requires the velocity of sound in the lens, which may be age-dependent, whereas Scheimpflug photography requires knowing the refractive index of the cornea, the anterior chamber, and the eye lens to enable correction of the photographs for the distortion due to the refraction of the cornea and lens ͑after Dubbelman et al 8 ͒. One of the major advantages of the algorithm described in this paper is the fact that it is based on digital-CCD-recorded Scheimpflug photographs instead of digitally scanned Scheimpflug photographs ͑see Richards et al 4 and Kampfer et al 5 ͒. Thus, additional errors are avoided in the analysis of the original Scheimpflug photographs, namely inaccuracies that occur by processing and scanning of the original Scheimpflug photograph.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, both techniques, A scan ultrasonography and slitlamp Scheimpflug photography, have their respective drawbacks: ultrasonography requires the velocity of sound in the lens, which may be age-dependent, whereas Scheimpflug photography requires knowing the refractive index of the cornea, the anterior chamber, and the eye lens to enable correction of the photographs for the distortion due to the refraction of the cornea and lens ͑after Dubbelman et al 8 ͒. One of the major advantages of the algorithm described in this paper is the fact that it is based on digital-CCD-recorded Scheimpflug photographs instead of digitally scanned Scheimpflug photographs ͑see Richards et al 4 and Kampfer et al 5 ͒. Thus, additional errors are avoided in the analysis of the original Scheimpflug photographs, namely inaccuracies that occur by processing and scanning of the original Scheimpflug photograph.…”
Section: Discussionmentioning
confidence: 99%
“…However, for a quantitative evaluation, for which especially digital Scheimpflug photographs are suitable, optical/refractive distortions must be taken into account. Such distortions arise not only from the anterior corneal surface ͑ACS͒ alone; images of deeper structures of the eye such as the posterior corneal surface, the pupil, and the anterior lens surface are also distorted [2][3][4][5] due to the differences in refractive indices and the various radii of curvature of the refractive surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,19 In our previous study with the Corvis ST (OCULUS Optikgeräte GmbH), the directly measured CCT at highest concavity was found to be reduced by ∼8% in 42 healthy subjects 20 without considering the Scheimpflug distortion. 21 The overall objective of our study is to predict the influence of Scheimpflug distortion on the CCT measurement, to propose a method to correct the distortion for dynamic CCTs, and to apply the method to study the CCT variation in clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…An early study reported that the directly observed CCT was underestimated by ∼43% in comparison with the true value. 21,23 The authors corrected this error by using the ray tracing technique with a Basic program. An introduction to the theory of ray tracing and its computation implementation can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%